Antimicrobial properties of Graphene sheets embedded with Titanium Oxide and Calcium Oxide nanoparticles for industrial wastewater treatment - Reza Darini; Hamed Ahari; Amir Khosrojerdi; Behrooz Jannat; Hossein Babazadeh (Scientific Reports)
Abstract This study investigated the antimicrobial efficacy of graphene, titanium dioxide nanoparticles (TiO2NPs), and calcium oxide nanoparticles (CaONPs) against various microorganisms in dairy wastewater. The minimum inhibitory concentration (MIC) of graphene was determined to be 41.66 mg/L for Escherichia coli and 33.33 mg/L for Staphylococcus aureus, outperforming TiO2NPs and CaONPs. Additionally, graphene sheets embedded with 2.8% TiO2 (GST2.8) demonstrated superior performance in inhibiting bacterial growth compared to unmodified or other modified graphene sheets. The GST2.8 treatment significantly reduced microbial counts for S. aureus, E. coli, and mold/yeast, with the lowest observed counts being 4.85 CFU/mL, 3.00 CFU/mL, and 4.04 CFU/mL, respectively. These results suggest that graphene-based nanocomposites incorporating TiO2NPs and CaONPs hold promise as effective antimicrobial agents for wastewater treatment applications.